Pembatalan Keputusan Pemberhentian dengan Hormat sebagai Aparatur Sipil Negara : Suatu Perspektif Tata Usaha Negara - Abdul Madjid Podungge; Fadel Ilato; Rizki Ayundari Putri (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
Civil servants play a crucial role in governance and development to achieve the national goals as stipulated in the Preamble to the 1945 Constitution of the Republic of Indonesia. Civil servants (PNS) are the primary foundation for the implementation of the Indonesian government system, as they implement public policy and provide public services. Their integrity, competence, and legal status significantly determine the quality of government bureaucracy. This study aims to determine the role of the Regional Civil Service Agency (BKD) in handling cases involving civil servants using fake diplomas during recruitment or promotion. The approach used is normative juridical, reviewing existing regulations, such as Law Number 5 of 2014 concerning the State Civil Apparatus, Government Regulations, and other technical regulations. Data were also obtained through interviews with BKD officials and analysis of relevant case documentation. The results of the study indicate that in practice, there is still a discrepancy between established legal procedures and their implementation in the field. Several cases indicate that administrative sanctions or termination of civil servants found to have used fake diplomas have not been fully based on proper verification and sanction mechanisms. This raises doubts about the validity of decisions and has the potential to undermine public trust in government institutions. This study emphasizes the importance of enforcing administrative discipline and improving internal oversight systems, as well as the need for stricter and more coordinated regulations between central and regional agencies to ensure that every administrative action has a valid legal basis. Implementing the principles of accountability and transparency in personnel management must be a priority to create a clean and professional bureaucracy.